Vaccine Law and Policy - Yang, Y. Tony.; Reiss, Dorit R. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Vaccine Law and Policy is the first book on vaccine law and policy written specifically for the general public or an educated lay audience without legal background. It offers comprehensive but accessible coverage of key aspects of vaccine law and policy, from product development and intellectual property protections, to regulation, public mandates, and vaccine injury claims. The COVID-19 pandemic sparked a growing interest in learning more about vaccine law and policy, as vaccine development, access, safety and requirements became relevant to hundreds of millions of people worldwide. This book covers United States law in most detail, but the developments and trends described have parallels in many countries, and the United States model and its actions influence others. Some of the most widely used vaccines against COVID-19 - mRNA vaccines - were developed in the United States, and choices made in the United States impact other countries. United States law currently has so much to say about vaccines. From the federal mandate President Biden enacted requiring federal employees to be vaccinated against COVID-19, to the growing number of private employers requiring vaccines to return to work, vaccine law has become a prevalent topic in everyday life. But there is little writing about the legal aspects of vaccines directed at the general public or an educated lay audience without a legal background. Vaccine Law and Policy will not only be invaluable to professionals implementing vaccine law and policy, but also to regulators, public health officials, and scientific researchers. Vaccine Law and Policy covers the wide range of laws and policies that impact the field. These include, among others, regulatory oversight by the FDA, one of the most influential bodies in drug and vaccines regulation worldwide, enforcement, and regulation of the research and development of vaccines; vaccine mandates for children and in the workplace, and medical, religious, and philosophical exemptions to them; patent law and other intellectual property protections such as trademark, trade secret, unfair competition, and copyright law; compensation for vaccine injuries under the National Vaccine Injury Compensation Program (NVICP) and other avenues of liability; safety monitoring; access to vaccines, their promotion, and issues related to funding and costs. The book will also discuss issues related to anti-vaccine movements and vaccine advocacy.
1. Introduction: Vaccine Basics, Balance of Interests, and the Legal Framework -- Part I: Vaccine Regulation and Monitoring -- 2. Regulation and Testing of Vaccines -- 3. Postmarket Vaccine Safety -- 4. Vaccines and Intellectual Property -- 5. Vaccine Injury Compensation in the United States -- 6. Immunization Information Systems -- 7. Vaccine Regulation in Global Comparison -- Part II: Equity and Vaccines -- 8. Funding Vaccinations in the United States -- 9. Vaccine Equity -- 10. Vaccine Access in Global Comparison -- Part III: Individual Decision Making and Vaccines -- 11. Informed Consent -- 12. Adolescent Consent -- 13. Tort Liability for Failure to Vaccinate -- Part IV: Vaccine Mandates -- 14. Introduction to Vaccines Mandates in the United States -- 15. School Vaccine Mandates and Exemptions -- 16. Workplace Vaccine Mandates -- 17. Federal Vaccine Mandates -- 18. Vaccine Mandates in Global Comparison -- 19. Vaccine Passports for Travel -- Part V: Special Contexts -- 20. Military Vaccinations -- 21. Vaccine Policy in Emergency Situations -- 22. Regulating Vaccine Misinformation Online -- Part VI: Policy -- 23. Vaccine Incentives and Health Insurance Surcharges -- 24. Vaccine Advocacy, Politics, and Anti-vaccine Movements.
Keywords: Medical laws and legislation; Private international law; Conflict of laws; International law; Comparative law; Political planning; Medical Law; Private International Law, International and Foreign Law, Comparative Law; Public Policy